High-Performance Visible-Blind Ultraviolet Photodetector Based on IGZO TFT Coupled with p–n Heterojunction - Yu, Jingjing; Javaid, Kashif; Liang, Lingyan; Wu, Weihua; Liang, Yu; Song, Anran; Zhang, Hongliang; Shi, Wen; Chang, Ting-Chang; Cao, Hongtao (ACS applied materials & interfaces, 2018)
A visible-blind ultraviolet (UV) photodetector was designed based on a three-terminal electronic device of thin-film transistor (TFT) coupled with two-terminal p–n junction optoelectronic device, in hope of combining the beauties of both of the devices together. Upon the uncovered back-channel surface of amorphous indium–gallium–zinc-oxide (IGZO) TFT, we fabricated PEDOT:PSS/SnO x /IGZO heterojunction structure, through which the formation of a p–n junction and directional carrier transfer of photogenerated carriers were experimentally validated. As expected, the photoresponse characteristics of the newly designed photodetector, with a photoresponsivity of 984 A/W at a wavelength of 320 nm, a UV–visible rejection ratio up to 3.5 × 107, and a specific detectivity up to 3.3 × 1014 Jones, are not only competitive compared to the previous reports but also better than those of the pristine IGZO phototransistor. The hybrid photodetector could be operated in the off-current region with low supply voltages (<0.1 V) and ultralow power dissipation (<10 nW under illumination and ∼0.2 pW in the dark). Moreover, by applying a short positive gate pulse onto the gate, the annoying persistent photoconductivity presented in the wide band gap oxide-based devices could be suppressed conveniently, in hope of improving the response rate. With the terrific photoresponsivity along with the advantages of photodetecting pixel integration, the proposed phototransistor could be potentially used in high-performance visible-blind UV photodetector pixel arrays.